Dissemination of Parenting Knowledge for Students’ Parents of SMP Muhammadiyah 7 Yogyakarta - Permadi, Aad Satria; Permatasari, Shearly Aulia; Sakinah, Canting Mutiara (Devotion : Jurnal Pengabdian Psikologi, 2025)
Parents of students at SMP Muhammadiyah 7 Yogyakarta who are raising teenagers for the first time often face difficulties in parenting. They do not know how properly care for teenagers. This parenting training aims to provide knowledge and methods to for raising teenagers. The training is carried out using lecture and discussion methods. The effectiveness of the training was measured using the Brief  Parenting Scale with pre-test and post-test assessments. The pre-test results showed that 20 parents of students had scores in the over-activity aspect in the high category, while the laxness aspect was in the medium and low categories. This indicates that the main parenting problem among these parents is a high level of over-activity. The focus of the training is to reduce the over-activity aspect to medium or low level. The t-test analysis of the pre-test and post-test measurements on the over-activity aspect showed a p <0.001 with a mean difference of 7.25. The pre-test mean was 15.6 (high category), while the post-test mean was 8.35 (medium category). Thus, parenting training for parents of Muhammadiyah 7 Yogyakarta middle school students has proven to be effective.